Sampling Problem for Non-separated Sets and Divided Differences - Avdonin, S.A.; Ivanov, S.A. (Sampling theory in signal and image processing, 2009)
An approach to solving sampling and interpolation problems in the case of non-separated sequences is developed. The approach is based on the duality between Riesz bases of exponential divided differences and group sampling and interpolating sequences. The complete description of group sampling and interpolating sequences for the Paley-Wiener spaces is obtained and stability properties of these sequences are discussed.